PENERAPAN MODEL REALISTIC MATHEMATICS EDUCATION (RME) PADA MATERI PENJUMLAHAN BILANGAN CACAH SISWA KELAS 1B SD NEGERI PALEBON 01 SEMARANG - Sriyani Sriyani; Henry Januar Saputra; Sukamto Sukamto (Universitas PGRI Yogyakarta, 2020)
The purpose of this study was to determine whether the application of realistic mathematics education models in mathematics learning in addition material in class I B students at SDN Palebon 01 Semarang 2020 increased. The subjects of this study were students of class I B SDN Palebon 01 Semarang, totaling 28 students from 11 female students and 17 male students. This type of classroom action research (CAR) uses data from observation, documentation and tests in a cycle consisting of 4 stages, namely planning, implementation, observation and reflection.The results of the study can be mathematics learning material addition in the application of realistic mathematics education models can improve student learning outcomes class I B SDN Palebon 01 Semarang. The statement was proven by learning activities that increased the average value of 54 in the first cycle and an average of 82 cycles. The increase in learning activities from the pre-test questions by 71% has not been completed (20 students) and 29% (8 students) in the second cycle increased to 89% by 25 and 11% (3 students) it shows that it has reached the minimum completeness criteria (KKM). Based on the results of this studysuggestions that can be submitted for teachers to innovate learning with the media and combine realistic mathematics education models to make it more fun and meaningful for students.